New insights on Leptospira sp. infection in ewes maintained in field semiarid conditions - Santos, Julio Cesar de Araujo (2022)
Leptospirosis is poorly studied in small ruminants raised in field semiarid conditions. In this study we compared serological, bacteriological and molecular diagnostic methods in ewes maintained in field Brazilian semiarid conditions. Blood, vaginal fluid and urine samples were collected from 60 Morada Nova ewes raised in a semi-intensive system in the Brazilian semiarid. Diagnostic tests performed were microscopic agglutination test (MAT), polymerase chain reaction (PCR) and bacterial isolation. Anti-Leptospira sp. antibodies were found in eight (13.33%) animals analyzed by MAT at reciprocal titer 25 (cut-off 25), while Leptospira sp. DNA was detected in urine or vaginal fluid of 56 animals (93.33%). There was growth of leptospires in 10 urine cultures and in 11 vaginal fluid cultures, however, two of urine (2/60–3.33%) and eight cultures of vaginal fluid (8/60–13.33%) were confirmed by PCR. Two samples of vaginal fluid (one of each animal) were submitted to sequencing demonstrating 99% similarity with L. santarosai and L. interrogans. The highest MAT sensitivities were obtained with reciprocal titer 25 (cut-off 25) compared to 50 and 100. The performance of different diagnostic techniques for leptospirosis in ewes raised in field semiarid conditions allowed a better evaluation of the herd, as well as made it possible to identify carrier animals. Genital route may be important for efficient transmission and without dependence on environmental factors in ewes from semiarid, as well as it's highlighted that titer 1:25 in serology was more efficient, indicating its use in ewes in field semiarid conditions.